Heartbeats Detector (Pendeteksi dan Pengukur Detak Jantung) - Annisa, Annisa; Billhaq, Mohammed Sultan; Rivai, Agung Wibisono (LPPM Universitas Negeri Jakarta, 2018)
Body health needs to be considered for everyone, especially heart health. The heart is one of the important organs possessed by humans that function to pump blood throughout the body and recovered after cleaning the lung organ. BPM (Beats Per Minute) is a parameter to show the condition of the heart, and the way to know the condition of the heart is to know the frequency of the heartbeat. Cases of death often occur in the health or medical field. One of them is the delay in knowing the condition of one's body. Because of the problem it needs a technology that can alleviate various problems arising in the medical world today.So made